Effect of Time and Voltage on Pollutant Remover in Gold Treatment Wastewater With Electrocoagulation Batch Reactor - RR Dina Asrifah; Titi Tiara Anasstasia; Mia Fitri Aurilia (Elkawnie, 2021)
Abstract: Wastewater from gold treatment by amalgamation has a high TSS value and heavy metal content in the form of Cu and Hg. This content can endanger the surrounding environment. Therefore, wastewater must be treated until it shows results below the permitted quality standards. Wastewater treatment is carried out using the batch reactor electrocoagulation method. The purpose of this study was to determine the efficiency value and optimal conditions by reducing the TSS, Cu, and Hg content in wastewater based on the effect of time (10 minutes) and voltage (4.5 volts, 6 volts, and 7.5 volts). This calculation of the efficiency and analysis showed that the optimal conditions occurred at a voltage of 6 volts from the three parameters, there are TSS = 97.49%, Cu = 95.71%, and Hg = 98.95%. Based on the test results after treatment, the wastewater still needs to be treated until it is below the safe quality standard according to Government Regulation of Indonesia Republic No. 82 of 2001 class 4.Abstrak: Air limbah pencucian emas dengan metode amalgamasi memiliki nilai TSS yang tinggi dan kandungan logam berat berupa Cu dan Hg. Kandungan tersebut dapat membahayakan lingkungan sekitar. Oleh karena itu, air limbah harus diolah hingga menunjukkan hasil di bawah baku mutu yang diizinkan. Pengolahan air limbah dilakukan dengan metode elektrokoagulasi reaktor batch. Tujuan penelitian ini adalah untuk mengetahui nilai efisiensi dan kondisi optimal dengan mereduksi kandungan TSS, Cu, dan Hg pada limbah cair berdasarkan pengaruh waktu (10 menit) dan tegangan (4,5 volt, 6 volt, dan 7,5 volt). Hasil perhitungan efisiensi dan analisis ini menunjukkan bahwa kondisi optimal terjadi pada tegangan 6 volt dari ketiga parameter yaitu TSS = 97,49%, Cu = 95,71%, dan Hg = 98,95%. Berdasarkan hasil pengujian setelah diolah, air limbah masih perlu diolah hingga berada di bawah baku mutu aman sesuai dengan PP RI No. 82 Tahun 2001 pada kelas 4.